VD_FINDINFO HC / 2014 / 500 vom 9. Mai 2014 - VD Tribunal cantonal (2014)
BAIL À LOYER, DÉFAUT DE LA CHOSE, DÉFAUT ESTHÉTIQUE, FRAIS ACCESSOIRES, POUVOIR D'APPRÉCIATION | 256 al. 1 CO, 257a al. 2 CO, 259a al. 1 CO, 274d al. 3 CO